Mouse soup - Lobel, Arnold (New York : HarperCollins, 1977)
A mouse convinces a weasel he needs the ingredients from several stories to make a tasty mouse soup.
Elem. School Library Collection, June 2000.
School Library Journal, September 2003.
Booklist, September 2003.
New York Times, May 2004.
Horn Book, February 2005.
Bulletin (Center for Children's books), August 2003.
Keywords: Mice -- Fiction; Readers (Elementary)